A reminder of the place of morphology and the H‐score in the diagnosis of hemophagocytic lymphohistiocytosis (HLH). Issue 3 (6th February 2018) - Favresse, J.; Lardinois, B.; Chatelain, B.; Mullier, F.; Jacqmin, H.
Key Clinical Message: This case report reminds the reader of the place of hemophagocytosis and the H‐Score in the diagnosis of secondary hemophagocytic lymphohistiocytosis. Abstract : This case report reminds the reader of the place of hemophagocytosis and the H‐Score in the diagnosis of secondary hemophagocytic lymphohistiocytosis.